Understanding the Barriers to COVID-19 Vaccine Among Hispanic/Latinx Communities - Razel Bacuetes Milo; Claudia Aguayo; Allison Rae Chico; José Andrés Rozo; Iris Vásquez; Patricia Calero; Joseph Burkard (SAGE Publishing, 2023)
Objective: COVID-19 disproportionally affected Hispanic/Latinx populations exacerbating systemic health inequities. The pilot study aimed to explore barriers to COVID-19 vaccination across Hispanic/Latinx communities in Southern California. Methods: Cross-sectional survey of 200 participants to identify common barriers to vaccine hesitancy among Hispanics/Latinx individuals in Southern California utilizing a 14-item survey and questionnaire in English and Spanish. Results: Of the 200 participants that completed questionnaires, 37% identified a knowledge deficit, 8% identified misinformation, and 15% identified additional barriers such as awaiting appointments, immigration status, transportation issues, or religious reasons as barriers to not receiving the COVID-19 vaccine. Wald statistics denoted that household members with COVID-19 infection within the past 3 months saw a medical provider within the last year, wearing a mask in public often, and barriers to vaccination (not knowing enough about the vaccine) predicted vaccine. These variables indicated changes in the likelihood of obtaining vaccination. Conclusion: The most crucial factor for increasing vaccination rates was directly reaching out to the community and actively conducting surveys to address the barriers and concerns encountered by Hispanic/Latinx participants.